“People Trapped Inside Shincheonji”: Broadcasting the Darker Side of Deprogramming - Di Marzio, Raffaella (The journal of CESNUR, 2020)
This article is an in-depth critical examination of the first two episodes of the TV show “People Trapped into Shincheonji” from a psychological perspective. The show was produced by the Christian Korean TV network CBS, which broadcast it in 2017. We see in the show the deprogramming procedure, captured with a hidden camera in Christian counseling centers, conducted with the aim of “rescuing” young women affiliated with Shincheonji, a Christian new religious movement experiencing a sustained growth in South Korea. The episodes are analyzed with reference to the vast literature on deprogramming, and the personal experience of the author, who interviewed a young woman deprogrammed in Italy in the late 1980s.